Funding liquidity, market liquidity and TED spread: A two-regime model - Kris Boudt; Ellen C.S. Paulus; Dale W.R. Rosenthal (National Bank of Belgium, 2013)
We investigate the effect of market liquidity on equity-collateralized funding accounting for endogeneity. Theory suggests market liquidity can affect funding liquidity in stabilizing and destabilizing manners. Using the average fee on stock loans as a proxy for equity-collateralized funding liquidity, we confirm the existence of these two regimes over the period of July 2006 – May 2011. Furthermore, we show that we can separate the two regimes using the yield spread of Eurodollars over T-bills (TED spread) and that a regime switch seems to occur near a TED spread of 48 basis points.
Keywords: G01; G18; 330; equity-collateralized funding liquidity; market liquidity; two-regime model; financial distress; Liquiditätseffekt; Kreditderivat; Kreditsicherung; Finanzkrise; USA